Programmable DC Motor Position Using Fuzzy Logic Controller - Mohamad Kamal, Nur Azieyatul Akmal; Dirman Hanafi,; Abdul Rahman, Hisyam (Evolution in Electrical and Electronic Engineering, 2023)
This study aims to control the position of DC (direct current) motors using STM32 F411RE. The STM32 is used as an interface card between MATLAB Simulink, a platform for developing controllers, and a DC motor, the position can be controlled by a fuzzy controller. As a result, a programmable DC motor position controller utilizing fuzzy logic is successfully designed for hardware and Simulink MATLAB. It can also connect a DC motor to a computer using the STM32 NUCLEO-F411RE card as an interface for MATLAB. As a result, the FLC controller has a quick response due to the smaller average of rise time, settling time, and peak time rather than the proportional–integral – Derivative (PID). Other than that, FLC with a small overshoot, output angle is more accurate and precise as compared to the PID controller. It can be proven by the data that have been evaluating if program the desired angle to 90° to both controllers FLC it has lower overshoot with 0.08313% compared to PID controller with 19.4172%, FLC has fast peak time with 1.09617s compared to the PID is 1.1379s. FLC also has a fast transient time and settling time of 1.0922s compared to PID 1.9834s. By comparing the controller by program, the desired input is 180 degrees. FLC has a lower overshoot with 0.0835% approximately 0% compared to the PID controller which has reached 17.5621%. FLC also has a fast peak time of 1.1787s with a peak of 180.5° close to the desired angle compared to the PID is 2.1844s and a peak of 216.8°, and the result shows FLC has a fast response to the system due to the fast transient time and settling time with 1.1668s compare to PID 2.1844s.